The Mapping of Huma Betang Character in Physics Learning Based on Machine Learning (Artificial Neural Network and Fuzzy C-Means) - Pri Dinata; Desy Kumala Sari; Theo Jhoni Hartanto; Gunarjo Suryanto Budi (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2026)
Background: Huma Betang (big house) is a philosophy of the Dayak community and serves as a value instilled in learning at schools in Central Kalimantan. While numerous studies have explored the application and inculcation of Huma Betang character values in students, few have quantitatively measured and mapped these characters as part of educational evaluation. Objective: This study aims to map the profile of the Huma Betang character in Physics learning among high school students in Palangka Raya City, Central Kalimantan. The characters measured in this study consist of four pillars: Hapahari (kinship), Handep (mutual assistance), Belom Bahadat (civilized living), and Hapakat Kula (mutual consensus). Method: This study utilized R-Studio software with the Artificial Neural Network (ANN) algorithm to predict character profiles and Fuzzy C-Means (FCM) to cluster the levels of the Huma Betang character, which were then compared with the Ideal Standard Deviation (ISD) categorization. This research is a descriptive study involving 290 students from schools in the center and outskirts of Palangka Raya city. The instrument used was in the form of a Situational Judgement Test (SJT) consisting of 23 statement items for the four pillars of Huma Betang. Results: The Ideal Standard Deviation, Artifial Neural Network, and Fuzzy C-Means analyses revealed the existence of six categories: very weak (1), weak (12), moderate (97), lower-strong (80), upper-strong (83), and very strong (17). The strong category contains the most student number, which mean Huma Betang character has been internalized by student in Palangka Raya. Conclusion: The triangulation of the three analytical methods provided a comprehensive profile of Huma Betang character, allowing for more targeted character-building interventions, specifically through the integration of students' specific roles in practical activities and physics projects.